IMMOBILE TRACE ELEMENT SYSTEMATICS OF OCEANIC ISLAND BASALTS: THE ROLE OF OCEANIC LITHOSPHERE IN CREATING THE GEOCHEMICAL DIVERSITY - Sayit, Kaan (Ofioliti, 2013)
The Earth’s mantle is known to be heterogeneous at different scales, which has been generally linked to the presence of diverse mantle reservoirs, some of which are believed to have remained isolated for long periods of time. When oceanic island basalts (OIBs) are subdivided into five distinct end-member groups on the basis of Sr-Nd-Pb isotope systematics, which include DM, EM1, EM2, HIMU and C, trace element systematics do not appear to be effective discriminators as isotopes, though an end-member signature may become dominant relative to others within a specific ratio range. Melting of a lithologically heterogeneous source or melting of distinct sources, which is followed by melt mixing, appears to be an important mechanism in creating variable geochemi- cal signatures in OIB genesis. Ratio-based trace element modeling suggests that sole involvement of eclogitic components cannot explain the entire elemental variation observed in OIBs; a peridotitic component must have been involved in the genesis of all types of end-member signatures. Combined trace element and isotope systematics are consistent with the involvement of metasomatized oceanic lithosphere (crust + lithospheric mantle) with/without sediments. This mechanism, which involves slab components uprising within the plumes, may also have been the main reason causing the geochemical diversity in the Tethyan mantle.